PENGARUH KOMPOSISI DEWAN KOMISARIS INDEPENDEN TERHADAP KINERJA PERUSAHAAN YANG DIMEDIASI OLEH MANAJEMNE LABA PADA PERUSAHAAN FARMASI DI INDONESIA - B51111140, Dewi Anggraini (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This research aims to find either the was or not the influence of independent commissioner board composition towards company performance that was mediated by earnings management. The independent commissioner board composition was measured by the percentage of the amount of independent commissioner towards the sum of commissioner board members. Earnings management was measured based on working capital accrual towards sales. Company performance was measured by Tobin’s Q ratio The population of this research was pharmaceutical companies which were listed in Indonesian Stock Exchange on 2010-2014. After purposive sampling method and outliers selection was used, the amount of the observations were 30. Multiple regression was used for analyzing. The results of this research indicate that (1) independent commissioner board composition influence company performance significantly; (2) independent commissioner board composition did not influence earnings management significantly; (3) earnings management did not influence company performance significantly; (4) independent commissioner board composition did not influence company performance significantly that was mediated by earnings management. Keywords : independent commissioner, earnings management, company performance, mediating.